A physics-based model of gate-tunable metal–graphene contact resistance benchmarked against experimental data. (12th May 2015) - Chaves, Ferney A; Jiménez, David; Sagade, Abhay A; Kim, Wonjae; Riikonen, Juha; Lipsanen, Harri; Neumaier, Daniel
Abstract: Metal–graphene contact resistance is a technological bottleneck in the realization of viable graphene-based electronics. We report a model that is useful for finding the gate-tunable components of this resistance, determined by the tunneling of carriers between the 3D metal and 2D graphene underneath, followed by Klein tunneling to the graphene in the channel. This model quantifies the intrinsic factors that control that resistance, including the effect of unintended chemical doping. Our results agree with experimental results for several metals.